Secured personal health records using pattern-based verification and two-way polynomial protocol in cloud infrastructure. (27th June 2022) - Indira, D.N.V.S.L.S.; Abinaya, R.; Chandanapalli, Suresh Babu; Vatambeti, Ramesh
This present research proposes the digitalised healthcare system that enables patients to generate, aggregate and store in the form of personal health records (PHRs). This requires more attention on cost effectiveness and less response time on public cloud platform. The existing cloud platforms have failed to implement the systemic approach for immediate verification and correction models on increasing PHR datasets. The storage and computation are two prime factors. Moreover, cloud systems need more attention on security and privacy breaches. In this proposed model the publisher-observer pattern-based healthcare systems allow the patients to verify and correct the PHRs before any type of computations. The cloud system acts as a backend framework that offers openness and easy accessibility. The experimental segment ensures the computational cost and response time for multiple polynomial PHR variations. The details evaluation also ensures the security and privacy preservation on sensitive healthcare datasets.